Effect of iodine doping on the electrical, thermal and mechanical properties of SnSe for thermoelectric applications. Issue 7 (15th February 2021) - Das, Amit; Chauhan, Avnee; Trivedi, Vikrant; Tiadi, Minati; Kumar, Ravi; Battabyal, Manjusha; Satapathy, Dillip K.
Abstract : We report the evolution of the thermoelectric and mechanical properties of n-type SnSe obtained by iodine doping at the Se site. Abstract : We report the evolution of the thermoelectric and mechanical properties of n-type SnSe obtained by iodine doping at the Se site. The thermoelectric performance of n-type SnSe is detailed in the temperature range starting from 150 K ≤ T ≤ 700 K. The power factor of 0.25% iodine doped SnSe is found to be 0.33 mW m −1 K −2 at 700 K, comparable to that of the other monovalent doped n-type SnSe. The temperature-dependent electrical conductivity of the undoped and iodine doped SnSe samples is corroborated by using the adiabatic small polaron hopping model. A very low value of thermal conductivity, 0.62 W m −1 K −1, is obtained at 300 K and is comparable to that of SnSe single crystals. The low thermal conductivity of n-type polycrystalline SnSe is understood by taking into account the anharmonic phonon vibrations induced by the incorporation of heavy iodine atoms at the Se sites as well as the structural hierarchy of the compound. Besides, iodine doping is found to improve the reduced Young's modulus and hardness values of SnSe, which is highly desirable for thermoelectric device applications.